Operationalising emergency care delivery in sub-Saharan Africa: consensus-based recommendations for healthcare facilities. Issue 8 (22nd July 2015) - Calvello, Emilie J B; Tenner, Andrea G; Broccoli, Morgan C; Skog, Alexander P; Muck, Andrew E; Tupesis, Janis P; Brysiewicz, Petra; Teklu, Sisay; Wallis, Lee; Reynolds, Teri
Abstract : A major barrier to successful integration of acute care into health systems is the lack of consensus on the essential components of emergency care within resource-limited environments. The 2013 African Federation of Emergency Medicine Consensus Conference was convened to address the growing need for practical solutions to further implementation of emergency care in sub-Saharan Africa. Over 40 participants from 15 countries participated in the working group that focused on emergency care delivery at health facilities. Using the well-established approach developed in the WHO's Monitoring Emergency Obstetric Care, the workgroup identified the essential services delivered—signal functions—associated with each emergency care sentinel condition. Levels of emergency care were assigned based on the expected capacity of the facility to perform signal functions, and the necessary human, equipment and infrastructure resources identified. These consensus-based recommendations provide the foundation for objective facility capacity assessment in developing emergency health systems that can bolster strategic planning as well as facilitate monitoring and evaluation of service delivery.